Perencanaan Pelaksanaan Program Supervisi Pengajaran di MI MPI Cendono - Ahmad Furqon Akhbar; Arumia Fairuz Husna; Luthfia Amanda Sari; Firda Fitrotul Unsa; Indra Lesmana (Universitas Negeri Malang, 2023)
Abstract: Education is one of the obligations that must be fulfilled by every child of the nation, so that they cancompete in the future and not be left behind by other countries. Educators are the key to studentsuccess in education. Therefore, educators who take the lead in educating their students must beguided and encouraged by teaching supervision so that educational success can increase. However,this actually raises the awareness of some educators about teaching supervision. Therefore, thepurpose of this research is to describe how educators perceive teaching supervision, especially at MIMPI Cendono. This research uses a qualitative approach with descriptive methods. Data collectiontechniques used are literature review and documentation study. The results showed that educators'perceptions of learning supervision included educator readiness in carrying out their duties, masteryof material, delivery methods, and educator discipline. The recommended teaching models in thesupervision program are Concept Acquisition Model, Inquiry Training Model, Nondirective LearningModel, Synthetic Model, Group Investigation Model, Jurisprudential Inquiry Model, ContingencyManagement Model, Training Model. Suitable social psychology learning supervision models areGroup Investigation and Jurisprudential Inquiry learning models.Keywords: education; supervision; teachingAbstrak: Pendidikan merupakan salah satu kewajiban yang harus dipenuhi oleh setiap anak bangsa, agardapat bersaing di masa depan dan tidak tertinggal dengan negara lain. Pendidik merupakan kuncikeberhasilan siswa dalam pendidikan. Oleh karena itu, pendidik yang memimpin dalam mendidikanak didiknya harus dibimbing dan didorong oleh pengawasan pengajaran agar keberhasilanpendidikan dapat meningkat. Namun, hal ini justru menimbulkan kesadaran sebagian pendidiktentang supervisi mengajar. Oleh karena itu, tujuan dari penelitian ini adalah untuk mendeskripsikanbagaimana pendidik mempersepsikan supervisi mengajar khususnya di MI MPI Cendono. Penelitianini menggunakan pendekatan kualitatif dengan metode deskriptif. Teknik pengumpulan data yangdigunakan adalah yaitu kajian literatur dan studi dokumentasi. Hasil penelitian menunjukkan bahwapersepsi pendidik terhadap supervisi pembelajaran meliputi kesiapan pendidik dalammelaksanakan tugasnya, penguasaan materi, metode penyampaian, dan kedisiplinan pendidik.Model pengajaran yang direkomendasikan pada program supervisi yaitu Model PemerolehanKonsep, Model Latihan Inquiry, Model Pembelajaran Nondirective, Model Sintetik, Model InvestigasiKelompok, Model Jurisprudential Inquiry, Model Contingensi Management, Model Pelatihan. Modelsupervisi pembelajaran psikologi sosial yang cocok yaitu Group Investigation dan modelpembelajaran Jurisprudential Inquiry.Kata kunci: pendidikan; supervisi; pengajaran